Localisation of members of the vascular endothelial growth factor (VEGF) family and their receptors in human atherosclerotic arteries. Issue 3 (27th February 2004) - Belgore, F; Blann, A; Neil, D; Ahmed, A S; Lip, G Y H
Abstract : Background: Vascular endothelial growth factor (VEGF) mediates endothelial cell mitogenesis and enhances vascular permeability. The existence of single or multiple VEGF isoforms and receptors suggests that these proteins may have overlapping but distinct functions, which may be reflected in their cell expression and distribution. Methods: The localisation of VEGFs A–C and their receptors (VEGFRs 1–3, respectively) in 30 fresh human atherosclerotic arteries, 15 normal uterine arteries, and 15 saphenous veins using immunohistochemistry and western blotting. Results: Saphenous veins showed no staining for VEGF-B or VEGFR-2. Smooth muscle cells (SMCs) showed the strongest staining for VEGF-A, VEGF-B, VEGFR-1, and VEGFR-2 in all specimens. Conversely, VEGFR-3 and VEGF-C were predominately localised to the endothelial vasa vasorum in normal arteries, whereas medial SMCs showed the strongest staining in atherosclerotic arteries. Western blotting showed variations in VEGF protein localisation, with lower amounts of VEGF-B and VEGF-C in saphenous veins, compared with arterial tissue. Amounts of VEGF-C were lower than those of VEGF-A and VEGF-B in all specimens. Conclusion: This study provides direct evidence of the presence of VEGF proteins and receptors in human physiology and pathology, with variations in both the amounts of VEGF proteins expressed and their cellular distribution in normal arteries compared with atherosclerotic arteries. The presence of VEGFs A–C and their receptors in normal arterial tissue implies that VEGF functions may extend beyond endothelial cell proliferation. Reduced VEGFR-2 staining in atherosclerotic arteries may have implications for the atherosclerosis process and the development of vascular disease and its complications.